Genetic testing for autonomic dysfunction or dysautonomias - Maltese, Paolo Enrico; Manara, Elena; Beccari, Tommaso; Dundar, Munis; Capodicasa, Natale; Bertelli, Matteo (Acta Biomedica Atenei Parmensis, 2020)
Background and aim: The autonomic system is made of two divisions called the sympathetic and parasympathetic nervous systems and extends from the central to the peripheral nervous system for controlling homeostasis. Autonomic dysfunction, also known as dysautonomia, occurs when the nerves that control involuntary bodily functions do not work properly. The aim of this mini-review is to summarize all the syndromes characterized by dysautonomia and for which the associated gene is known. Methods: We searched those syndromes in PubMed and OMIM database. Results: We found 36 genetic syndromes characterized by autonomic dysfunction. Conclusions: We propose genetic testing in all cases of idiopathic autonomic dysfunction. A genetic test with these genes would make it possible to determine the molecular diagnosis of new subjects and/or establish a risk of recurrence in family members for the purpose of planning appropriate preventive and/or therapeutic measures.